The Formalization of Islamic Sharia in Public Sphere: A Case Study of Hizbut Tahrir Indonesia - Gazali, Hatim (DINIKA : Academic Journal of Islamic Studies, 2017)
Following the stepped down of the New Order, the movements of establishing Islamic sharia in Indonesia has increased. Some of the organizations which promote Islamic sharia on their movements are Majelis Mujahidin Indonesia (MMI), Front Pembela Islam (FPI), and Hizbut Tahrir Indonesia (HTI). This paper observes the movements of HTI by using the perspective of public reason, especially the theories of John Rawls and Abdullah An-Naim. The results show that HTI should use more democratic methods in delivering its notion. As Indonesia is a democratic nation, creating the appropriate form of discussion and conversation would be an effective way in introducing Islamic sharia to the public. Later, the decision of accepting or rejecting the idea is in the hands of the public.